2012
DOI: 10.1155/2012/939350
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Simultaneous Liver Resection for Occult Liver Metastases of Pancreatic Adenocarcinoma

Abstract: Backround. Pancreas resection is the only curative treatment for pancreatic adenocarcinoma. In the event of unexpected incidental liver metastases during operative exploration patients were traditionally referred to palliative treatment arms. With continuous progress in the surgical expertise simultaneous pancreas and liver resections seem technically feasible nowadays. The aim of this study therefore was to analyze the impact of synchronous liver-directed therapy on operative outcome and overall survival in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
52
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(52 citation statements)
references
References 32 publications
0
52
0
Order By: Relevance
“…However, resection for metachronous liver metastases instead of gemcitabine might extend survival in highly selected patients. Meanwhile, Klein et al[50] reported that no similar survival was achieved by pancreatectomy and simultaneous liver resection for PDAC, albeit at a R0 status, compared with pancreatectomy for non-metastasized PDAC (13.0 mo vs 26.5 mo)[50] (Table 8). On the contrary, we showed that the survival of PDAC patients with synchronous liver metastasis who underwent simultaneous curative resections (15.7 mo) was not only longer than that of those who underwent palliative surgical bypass alone (4.4 mo) but also similar to that of patients with non-metastasized PDAC who underwent curative pancreatectomy alone (16.9 mo).…”
Section: Discussionmentioning
confidence: 99%
“…However, resection for metachronous liver metastases instead of gemcitabine might extend survival in highly selected patients. Meanwhile, Klein et al[50] reported that no similar survival was achieved by pancreatectomy and simultaneous liver resection for PDAC, albeit at a R0 status, compared with pancreatectomy for non-metastasized PDAC (13.0 mo vs 26.5 mo)[50] (Table 8). On the contrary, we showed that the survival of PDAC patients with synchronous liver metastasis who underwent simultaneous curative resections (15.7 mo) was not only longer than that of those who underwent palliative surgical bypass alone (4.4 mo) but also similar to that of patients with non-metastasized PDAC who underwent curative pancreatectomy alone (16.9 mo).…”
Section: Discussionmentioning
confidence: 99%
“…However, published data demonstrate that the procedure can be performed safely, but results are inconsistent as to whether complete resection of the PDAC with combined resection of liver metastases will lead to a survival benefit [30,[38][39][40][41][42][43]. Eight reports including more than 9 patients found median overall survival times between 5.9 and 11.4 months after resection [29,39,42,[44][45][46][47][48].…”
Section: Role Of Surgerymentioning
confidence: 99%
“…Klein et al [44] reported a median survival in PDAC patients with hepatic metastases of 7.6 months after resection. Within this small study, 22 PDAC patients who underwent synchronous, liverdirected therapy either with anatomical liver resection (7 patients (32%)) or atypical resection (15 patients (68%)) were analyzed.…”
Section: Role Of Surgerymentioning
confidence: 99%
“…In 2012, another study from Germany, this time from the Charite group, compared the outcomes of 22 patients who underwent simultaneous pancreas resection and liver‐directed therapy for pancreatic adenocarcinoma with 22 patients who underwent standard pancreatectomy for non‐metastasized PDAC in a matched pair study design . Although postoperative morbidity (≥Clavien 3) was higher in the LM group, the result was not statistically significant ( P = 0.099).…”
Section: Resultsmentioning
confidence: 99%
“…Klein et al . compared patients who underwent resection of PDAC and associated LM with those who only underwent standard pancreatectomy . In 2010, Seelig et al .…”
Section: Discussionmentioning
confidence: 99%